Prognostic values of S100 family members in ovarian cancer patients - Bai, Yang; Li, Liang-Dong; Li, Jun; Lu, Xin (BMC cancer, 2018)
Exhibiting high consistence in sequence and structure, S100 family members are interchangeable in function and they show a wide spectrum of biological processes, including proliferation, apoptosis, migration, inflammation and differentiation and the like. While the prognostic value of each individual S100 in ovarian cancer is still elusive. In current study, we investigated the prognostic value of S100 family members in the ovarian cancer. We used the Kaplan Meier plotter (KM plotter) database, in which updated gene expression data and survival information are from 1657 ovarian cancer patients, to assess the relevance of individual S100 family mRNA expression to overall survival in various ovarian cancer subtypes and different clinicopathological features. It was found that high expression of S100A2 (HR = 1.18, 95%CI: 1.04-1.34, P = 0.012), S100A7A (HR = 1.3, 95%CI: 1.04-1.63, P = 0.02),S100A10 (HR = 1.2, 95%CI: 1.05-1.38, P = 0.0087),and S100A16 (HR = 1.23, 95%CI: 1-1.51, P = 0.052) were significantly correlated with worse OS in all ovarian cancer patients, while the expression of S100A1 (HR = 0.87, 95%CI: 0.77-0.99, P = 0.039), S100A3 (HR = 0.83, 95%CI: 0.71-0.96, P = 0.0011), S100A5 (HR = 0.84, 95%CI: 0.73-0.97, P = 0.017), S100A6 (HR = 0.84, 95%CI: 0.72-0.98, P = 0.024), S100A13 (HR = 0.85, 95%CI:0.75-0.97, P = 0.014) and S100G (HR = 0.86, 95%CI: 0.74-0.99, P = 0.041) were associated with better prognosis. Furthermore, we assessed the prognostic value of S100 expression in different subtypes and the clinicopathological features, including pathological grades, clinical stages and TP53 mutation status, of ovarian cancer patients. Comprehensive understanding of the S100 family members may have guiding significance for the diagnosis and outcome of ovarian cancer patients.